2013
DOI: 10.5194/nhess-13-2851-2013
|View full text |Cite
|
Sign up to set email alerts
|

Pre-, co-, and post- rockslide analysis with ALOS/PALSAR imagery: a case study of the Jiweishan rockslide, China

Abstract: Abstract. On 5 June 2009, a catastrophic rockslide debris flow occurred at the crest of the Jiweishan range, Chongqing Municipality, China, killing 74 people and injuring an additional eight. We use L-band ALOS/PALSAR imagery to address landslide processes before, during and after the slide. We employ three different SAR methods, i.e., short baseline subsets (SBAS) interferometric SAR (InSAR), SAR backscattering intensity change, and InSAR stacking algorithm, to study any ground deformation before the rockslid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Del Ventisette et al, 2013;Deng et al, 2016;Hu, Li, Ding, Zhu, & Sun, 2013;Kim, Lu, Jia, & Shum, 2015) and landslides (e.g. Tong & Schmidt, 2016;Zhao, Kang, Zhang, Lu, & Li, 2018;Zhao, Lu, Zhang, & de La Fuente, 2012;Zhao et al, 2016Zhao et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Del Ventisette et al, 2013;Deng et al, 2016;Hu, Li, Ding, Zhu, & Sun, 2013;Kim, Lu, Jia, & Shum, 2015) and landslides (e.g. Tong & Schmidt, 2016;Zhao, Kang, Zhang, Lu, & Li, 2018;Zhao, Lu, Zhang, & de La Fuente, 2012;Zhao et al, 2016Zhao et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, polarimetric SAR data have been studied for terrain and land use classification. Various studies utilizing SAR data for landslide detection and characterization have been reported, even for these ten years (e.g., Cao et al 2008;Liao and Shen 2009;Christophe et al 2010;Dong et al 2011;Kawamura et al 2011;Furuta and Sawada 2013;Zhao et al 2013;Liu and Yamazaki 2015;Shibayama et al 2015;Tang et al 2015;Plank et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One of the advantages of the former is that they can treat surface changes or movements smaller than the wavelength of a SAR system. For example, Zhao et al (2013) analyzed the L-band Advanced Observing Satellite (ALOS) Phased Array-type L-band SAR (PALSAR) using the short baseline subset (SBAS) InSAR. They detected pre-rockslide movement of less than 50 cm within 184 days for the 2009 Jiweshan rockslide in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terrestrial subaerial geomorphology lidar is the remote sensing technique that has most recently contributed the most. Other techniques such as SAR (Synthetic Aperture Radar) offer opportunities to further investigate Earth surface processes such as landsliding (Roering et al ., ; Bovenga et al ., ; Berti et al ., ; Raucoules et al ., ; Zhao et al ., ) and to analyse river bed morphology (Marcus and Fonstad, ).…”
Section: Introductionmentioning
confidence: 99%